2019
DOI: 10.1038/s41467-019-09429-x
|View full text |Cite
|
Sign up to set email alerts
|

Excitation and coherent control of spin qudit modes in silicon carbide at room temperature

Abstract: One of the challenges in the field of quantum sensing and information processing is to selectively address and coherently manipulate highly homogeneous qubits subject to external perturbations. Here, we present room-temperature coherent control of high-dimensional quantum bits, the so-called qudits, associated with vacancy-related spins in silicon carbide enriched with nuclear spin-free isotopes. In addition to the excitation of a spectrally narrow qudit mode at the pump frequency, several other modes are exci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
75
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 34 publications
1
75
0
3
Order By: Relevance
“…Contrarily, the zero-field splitting of the centers V 2 centers in 4H-SiC in the excited state exhibits a large thermal shift, which makes them useful for thermometry applications [29]. All four ground state spin levels of V − Si have been used to demonstrate absolute dc magnetometry, which is immune to thermal noise and strain inhomogeneity [30].…”
Section: A Spin Centers In Silicon Carbidementioning
confidence: 99%
See 1 more Smart Citation
“…Contrarily, the zero-field splitting of the centers V 2 centers in 4H-SiC in the excited state exhibits a large thermal shift, which makes them useful for thermometry applications [29]. All four ground state spin levels of V − Si have been used to demonstrate absolute dc magnetometry, which is immune to thermal noise and strain inhomogeneity [30].…”
Section: A Spin Centers In Silicon Carbidementioning
confidence: 99%
“…However, the system can also undergo intersystemcrossing (ISC) to the shelving states |4 with the rates k 24 and k 34 [11]. From there the system returns to the ground state, with a bias for the state |1 over state |0 with the rates k 40 and k 41 [25,30,44]. The exact ISC rates from and to the shelving state are not yet known precisely but, by considering the recorded ODMR data shown in Fig.…”
Section: Energy Levels and Optical Pumpingmentioning
confidence: 99%
“…However, so far, no single-photon source in SiC has been proved experimentally to have single-photon indistinguishability as for other color centers in diamond such as NV and the silicon vacancy. Using the V Si in SiC, it has been demonstrated the manipulation and control of spin qudits (4 dimensions quantum states) [176], owing to the defect 4 projections of their spin states. Higher dimensions quantum states have shown promises to improve quantum metrology [177].…”
Section: Spin-photon Entanglement Interfaces For Quantum Metrology Anmentioning
confidence: 99%
“…In this letter, we report room temperature optically detected magnetic resonance (ODMR) experiments on an ensemble of V2 silicon vacancies in 4H-SiC. By using a two microwave frequency setup, the +1/2 ↔ −1/2 transition can be detected optically [2] [12]. Rabi oscillations of all three magnetic dipole allowed transitions are measured.…”
mentioning
confidence: 97%
“…For example, a dipole-like perturbation does not mix different order poles fixing the spin relaxation times such that T p = 3T d = 6T f , as recently discussed theoretically in the case of a fluctuating magnetic field acting on a silicon vacancy in SiC. [2] [3] An accessible spin 3/2 system for testing this prediction is the V2 silicon vacancy in 4H-SiC [2,4,5]. Recently, a number of groups have demonstrated that defects in SiC have optically accessible spins with coherence times on a par with diamond [5,6].…”
mentioning
confidence: 99%